Advances in Precise Structure Control and Assembly toward the Carbon Nanotube Industry. (5th December 2021) - Zhu, Zhenxing; Cui, Chaojie; Bai, Yunxiang; Gao, Jun; Jiang, Yaxin; Li, Bofan; Wang, Yao; Zhang, Qiang; Qian, Weizhong; Wei, Fei
Abstract: Carbon nanotubes (CNTs) possess a unique tubular structure composed of highly graphitized atoms. Since their sp 2 hybridized skeleton is discovered under the microscope, extensive attention is paid to their peculiar physics and extraordinary performances in mechanics, optics, and electricity. However, due to the challenges in controlled synthesis and mass production, there is a long bottleneck period in both the science and engineering of CNTs. In the recent decade, significant advances have emerged in ton‐scale production, 3D microprocessors, ultrastrong fibers, etc., which have pushed the renaissance of CNTs toward a new peak. This important progress benefits from the critical but commonly ignored breakthroughs in the precise structure control and assembly of CNTs. Herein, the morphological manipulation and technical routes toward the CNT industry will be focused on. First, the growth mechanism of defect‐free aligned CNTs will be discussed. Subsequently, nondestructive flow‐guided fabrication methods and their application paradigms are summarized. Then, attention will be turned to assembly‐based industrial production and applications of CNTs. Some research prospects toward the precise synthesis and CNT industry are proposed at last, in the hope of building a comprehensive understanding on the catalytic assembly toward defect‐free nanostructures and their high‐end applications. Abstract : Recent commercialization of carbon nanotubes (CNTs) much depend on the rapid development in precise structure control and morphological assembly technology. This review summarizes the catalytic growth mechanism of defect‐free CNTs. Then, template‐assisted morphological assembly is introduced as an efficient route toward their mass production. Finally, cutting‐edge applications with potential breakthroughs in energy and electronics are presented.